Work arrangements in digitally mediated care and domestic work - Friederike Molitor (Community, Work & Family, 2025)
As the need for care has grown, paid care and domestic work in the private home is increasingly being organised on the market. Today, digital platforms serve as intermediaries for care and domestic services but systematic research on the resulting work arrangements between workers and clients remains limited. By understanding platform-mediated care and domestic work arrangements as a (social) exchange of `love and money' between workers and clients, the study explores the working conditions and the worker-client relationships that emerge. Drawing on unique survey data collected on a large digital platform in Germany in 2019, the study shows that care and domestic workers who offer their services on digital platforms often experience informal work arrangements characterised by low working hours and irregular shifts. The worker-client relationships are described as amicable more than professional. They are often built on continuity, long-termism and reliability, which are essential for a lasting relationship. This challenges the ondemand, economic logic characterising other forms of platform work.
Keywords: 300; Care and domestic work; informality; platform work; love and money